(untitled) (Journal of the College of Basic Education, 2022)
At the beginning of the research and its importance, the two researchers touched on the interest in training goalkeepers in football for the halls, by introducing aids in the training process that contribute to preparing them within exercises according to the visual thinking network in improving self-confidence. As for the problem of the research, the researchers found by looking at the exercises in the football education teams for the halls and by noting a discrepancy in the level of skill performance of goalkeepers, which is attributed to poor self-confidence due to the lack of attention to the psychological aspect as well as the lack of use of the necessary tools allocated in the training units, which are It increases the motivation of goalkeepers to continue and perform with more motivation, as well as the development of the most important aspect is visual thinking, the most important of which is (symbols, images, .......) and thus these tools serve goalkeepers with the psychological aspect, thinking and performance in general. The study aimed to know the effect of exercises on self-confidence. Knowing the effect of exercises on some goalkeepers’ skills in futsal football. As for the research hypotheses, there are statistically significant differences between the results of the tribal tests and the results of the post tests for self-confidence in favor of the post tests for the sample under study. The researchers also touched on several researches related to training aids to learn about the basic skills and qualities needed by the goalkeeper. Some models of previous studies and similar to the research were presented to take advantage of them The researchers used the experimental method by designing a single group with a pre- and post-test to suit the nature of the study, as the research community was determined by goalkeepers, the second Baghdad educator, Karkh, and the research sample was chosen by the deliberate method, which numbered (6), where the exploratory experiment was conducted on (2) goalkeepers. They are from the research sample, then the researcher used the tribal tests for the research sample and then applied the special exercises using the means and tools prepared by the researchers, where he applied them in the main part of the training units A number of conclusions were reached, including: -The researchers’ use of the self-confidence scale positively affected the development of self-confidence and goalkeepers in futsal football. -The two researchers used special exercises within the visual thinking networks that I used in the main experiment to have a positive effect on the skill performance of short hand handling and short foot handling for the skills of goalkeepers in futsal football for players, as the results showed a clear superiority of the experimental group in the post tests over the tribal tests. In light of the conclusions reached by the researcher recommends the following: Working to benefit from the results of the current study by using special exercises (visual thinking networks) in training and giving them great importance during the training units during the special preparation period. For futsal goalkeepers, because of their importance in developing the intellectual side and perceptions of futsal goalkeepers. 2 -Attention to diversify the means and tools used in the training unit together and work to make them consistent with the requirements of goalkeepers in football for the halls.